Struggle for Recognition Theosophy in Early 20th Century Warsaw - Kotkowska, Karolina; Kasperek, Andrzej 1973- (2021)
The present study focuses on the activities of the first Polish Theosophical group, which for many reasons was never fully institutionallyrecognized. It was active from around 1905 and concentrated around Kazimierz Stabrowski (1869-1929), a Polish painter and the head of the Warsaw School of Fine Arts. The aim of this paper is to sociologically analyze this esoteric environment in Warsaw, which is treated here as an example of a cultic milieu from the perspective of visibility and recognition. Referring to the category of rejected knowledge (anomalies or the "cultural rubbish bin") and using the case of Stabrowski and other members of the group, the authors highlight their efforts in the struggle for the recognition of their ideas in various environments and trace the process of their exclusion. Further, they examine the status of the Theosophical current in the public discourse of the time, which was undoubtedly related to the scope of Theosophy itself, which largely focused on the liminal aspects of humanity and cognition.